Adoption and impact assessment of improved wheat technology on households´ wheat production in the Sudan - Hassan, Alawia; Hashim, Abdel Aziz; Fageer, Elrashid; Tahir, Izzat; Assefa, Solomon (المجلة الزراعية; مجلد 17 عدد 1 (2019), 2019)
Wheat is considered as one of the main cereals in the Sudan and the government considered domestic wheat production as a priority.  The objective of this study was to analyze adoption and estimate its impacts on wheat yield as a major farm level impact for Support to Agricultural Research for Development on Strategic Commodities project (SARD-SC ) implemented during the period from 2012-2016 in the Sudan. In order to estimate the determinants of adoption and to correct   the self selectivity bias in the project participation, the two- step Heckman model was used which estimated a probit regression equation in the first step and corrected the bias through including the inverse Mill’s ratio (IMR). To estimate the impact on wheat yield, the endogenous switching regression (ESR) model was used to estimate the average treatment effects resulting from the use of improved wheat varieties. The ESR model is potent in terms of correcting heterogeneity arising both from observed and non-observed household characteristics. The results showed that farmers’ participation in hosting demonstration plots, attending field days and training through farmers field schools within the SARD-SC project had significantly enhanced adoption of the recommended wheat package in Sudan. The coefficient of the IMR indicated that the non-observable factors such as farmers’ skills and motivations significantly decreased the area allocated for wheat and the use of Heckman’s model had corrected the bias arising from such factors. The estimated ESR model showed that adoption of the package increased wheat yield by 1.98 ton/ha and farmers participation with SARD-SC project significantly increased the probability to adopt improved varieties. It is concluded that the strategy of intervention by the SARD-SC project to enhance wheat production in the Sudan enhanced both adoption of the recommended package and increased wheat productivity. It is recommended to implement the SARD-SC technology transfer strategy in establishing innovation platforms with the participation of various stakeholders to increase adoption of the recommended wheat package and improve yield for enhanced food security in the Sudan.               محصول القمح من أهم محاصيل الغلال المستهلكة في السودان وتعطي الحكومة أولوية للإنتاج المحلى . هدفت هذه الدراسة لتحليل درجة تبنى الحزم التقنية المحسنة والمجازة وتقدير أثرها على إنتاجية القمح باعتبارها اهم اثر على المستوى المزرعي لمشروع بنك التنمية الافريقي لدعم السلع الغذائية في السودان(SARD-SC ) خلال الفترة من 2012 الى  2016. لتقدير محددات التبني ولتصحيح الاختيار الشخصي المتحيز للمشاركين في المشروع تم استخدام نموذج two – step Heckman  لمعرفة مقدرات معادلة الانحدار في المرحلة الأولى وتم إضافة Inverse Mill Ratio لتصحيح التحيز في المرحلة الثانية للانحدار الخطى لمساحة الأصناف المحسنة. لتقدير الأثر على إنتاجية القمح تم استخدام نموذج الانحدارendogenous switching regression  لمعرفة أثر متوسط المعالجة الناتجة من استخدام الأصناف المحسنة للقمح.  أوضحت النتائج أن المزارعين المشاركين في الحقول الإيضاحية والحضور في أيام الحقل والمتدربين في مدارس المزارعين ضمن نشاطات مشروع SARD-SC  تحسنت درجة التبني لحزمة أنتاج القمح الموصى بها في السودان لديهم وبدرجة معنوية. أوضحت مقدرات IMR  أن العوامل غير المتاحة مثل مهارات المزارعين والحوافز أدت إلى نقصان المساحة المتحولة لزراعة القمح وبدرجة معنوية كما أدى استخدام نموذج Heckman  لتصحيح التحيز الناتج من هذه العوامل. أوضحت مقدرات ESR  أن تبنى الحزم التقنية قد زاد من إنتاجية القمح بمقدار 1.98  طن/هكتار وأن المزارعين المشاركين بمشروع SARD SC قد زادوا احتمال تبنى الأصناف المحسنة بدرجة معنوية . أثبتت نتائج هذه الدراسة أن تدخل مشروع SARD-SC   أدى إلى تحسين درجة تبنى الحزم الموصى بها لإنتاج القمح بالسودان وبالتالي تحسين الإنتاجية . لذلك أوصت الدراسة بإنشاء المزيد من منصات الابتكار بمختلف مناطق إنتاج القمح بناءً على أنشطة مشروع  SARD SC لاستيعاب مزيداً من مزارعي القمح في السودان وذلك لتحسين الأمن الغذائي في السودان.